The Longitudinal Study of Measuring Corporate Tax Planning: Evidence from Industrial Product Companies - Nasir, Noor Emilina Mohd; Kamarudin, Siti Nurhazwani; Rashid, Norfadzilah; Yaacob, Najihah Marha (Indonesian Journal of Sustainability Accounting and Management, 2023)
This paper examines the extent of corporate tax planning undertaken by a sample of 43 Malaysian-listed industrial companies during the period from 2000 to 2020. This longitudinal study covers the period of tax and accounting reform in Malaysia. Descriptive statistics and t-tests were conducted to examine the differences among variables. This paper contributes to the analysis of whether there is a significant difference between corporate tax planning and the impact of tax and accounting reform in the Malaysian environment over the past 20 years. The results show that there is a significant difference between the effective tax rate and the statutory tax rate. This observation suggests that the tax planning strategies adopted by firms have the potential to reduce the amount of tax payable. Further research is needed to identify the factors that have an impact on the remarkable discrepancy between the two variables. The results of this study suggest that firms are using efficient tax planning techniques resulting in significant tax savings.